Composing place : digital rhetorics for a mobile world - Greene, Jacob (Jacob Wes) (Utah State University Press, 2023)
"Composing Place proposes an innovative approach to engaging with the compositional affordances of mobile technologies. Jacob Greene utilizes a rhetorical framework through which writers can leverage the affordances of new technologies and develops this framework by drawing on theoretical approaches within rhetorical studies, multimodal composition, and spatial theory" -- Provided by publisher.
Keywords: English language -- Rhetoric -- Study and teaching (Higher) -- Technological innovations.; Mobile computing -- Technological innovations.; Mobile computing -- Social aspects.; Mobile communication systems -- Technological innovations.; Mobile communication systems -- Social aspects.; Mobile communication systems in education.; Spatial behavior -- Social aspects.; Informatique mobile -- Innovations.; Informatique mobile -- Aspect social.; Radiocommunications mobiles -- Innovations.; Radiocommunications mobiles -- Aspect social.; Apprentissage mobile.; Rhetoric.; Technical Writing.; TECHNOLOGY & ENGINEERING.; Mobile communication systems in education; Mobile communication systems -- Technological innovations; Electronic books.